KAJIAN KANDUNGAN KAFEIN KOPI BUBUK, NILAI pH DAN KARAKTERISTIK AROMA DAN RASA SEDUHAN KOPI JANTAN (Pea berry coffee) DAN BETINA (Flat beans coffee) JENIS ARABIKA DAN ROBUSTA - Aditya, I Wayan; Nocianitri, Komang Ayu; Yusasrini, Ni Luh Ari (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 5 No 1 (2016): Jurnal ITEPA, 2016)
The aims this research was to determine the caffeine content of coffee powder, pH value and characteristics flavor and aroma steeping pea berry coffee and flat beans coffee type arabica and robusta. The research is an experimental research and the data were analyzed with descriptive method and variance, if significantly different to the observed variable, then continued with Duncan test. Description method used to reviewing the differences between caffeine content of coffee powder, pH value, flavor characteristics steeping pea berry coffee and flat beans coffee from arabica and robusta. The results showed that caffeine content of arabica coffee powder lower than robusta coffee powder, which 1.20 % in pea berry arabica coffee powder and 1.77 % in flat beans arabica coffee powder, whereas 2.01 % in pea berry robusta coffee powder and 1.99 % in flat beans robusta coffee powder. The pH value of the steeping coffee arabica lower than steeping coffee robusta, which pea berry Arabica coffee 5.23 and flat beans arabica coffee 5.16, whereas pea berry robusta coffee 5.69 and flat beans robusta coffee 5.61. Pea berry Arabica coffee flavor best compared with flat beans Arabica coffee, pea berry robusta coffee and flat beans robusta coffee.
Keywords: pea berry coffee, flat beans coffee, arabica and robusta.